Unveiling the drivers of geographic atrophy progression in eyes with reticular pseudodrusen - Mingui Kong; So Young Han; Sungsoon Hwang; Ga-In Lee; Je Moon Yoon; Don-Il Ham (PLoS ONE, 2025)
Purpose To evaluate the progression rate of geographic atrophy (GA) and identify factors associated with GA expansion in eyes with reticular pseudodrusen (RPD) using fundus autofluorescence (FAF) photography. Methods A total of 28 eyes from 28 patients diagnosed with GA and RPD, who completed a 3-year follow-up, was included. The eyes underwent thorough examination with color fundus photography, FAF and near infrared (NIR) imaging, and spectral domain optical coherence tomography (SD OCT). The areas of atrophic lesions were quantified using FAF images at years 1, 2, and 3 employing a semi-automated software (Region Finder). Results The rate of increase in mean GA area in eyes with RPD was calculated to be 0.39 ± 0.21 mm per year over the 3-year period. The annual progression rate measured over three years showed a statistically significant increase each year. Univariate analysis revealed that subfoveal choroidal thickness (SFCT) and RPD distribution were independently associated with GA progression (P ≤ 0.037). In multivariate analysis, thin SFCT was the only significant factor linked to an increased rate of GA growth. The progression from extrafoveal GA to foveal GA was solely associated with the initial square root GA area. Conclusion These results offer valuable insights for the development of interventional strategies aimed at mitigating GA enlargement in this specific subgroup of patients.